The Analysis of the Implementation of Cash Receipts and Disbursements Accounting System at Ibnu Sina Islamic Hospital Bukittinggi - Nadya Dwi Fortuna; Aga Arye Perdana; Yessi Yessi (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2026)
This study analyzes the implementation of the accounting system for cash receipts and expenditures at Ibnu Sina Islamic Hospital Bukittinggi. The qualitative method was employed with data collection through interviews, observation, and documentation. Results indicate that the current cash management system follows a clear workflow with function segregation and supporting documentation. Challenges include manual recording errors due to Microsoft Excel usage, delayed BPJS and insurance claims causing receivables backlog, lengthy bureaucratic authorization processes, and limited human resources in the finance department. Additionally, the accounting information system lacks full integration with hospital management and banking systems, slowing financial reporting and increasing error risks. The study recommends developing an integrated computer-based accounting information system, routine staff training, and digital authorization to enhance financial management efficiency. Abstrak Penelitian ini bertujuan untuk menganalisis penerapan sistem akuntansi penerimaan dan pengeluaran kas pada Rumah Sakit Islam Ibnu Sina Bukittinggi. Metode penelitian yang digunakan adalah kualitatif dengan teknik pengumpulan data melalui wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa sistem pengelolaan kas rumah sakit telah memiliki alur yang jelas dan memenuhi prinsip pemisahan fungsi serta kelengkapan dokumen pendukung. Namun, terdapat beberapa kendala seperti kesalahan pencatatan akibat penggunaan Microsoft Excel secara manual, keterlambatan klaim BPJS dan asuransi yang menyebabkan penumpukan piutang, proses birokrasi otorisasi yang panjang, serta keterbatasan sumber daya manusia pada bagian keuangan. Sistem informasi akuntansi yang digunakan belum terintegrasi penuh dengan SIMRS dan perbankan sehingga memperlambat proses pelaporan keuangan dan meningkatkan risiko kesalahan. Penelitian menyarankan pengembangan sistem informasi akuntansi berbasis komputer terintegrasi, pelatihan rutin bagi staf, serta penerapan otorisasi digital untuk meningkatkan pengelolaan keuangan.